Stability analysis of the shape factor effect of radiative on MHD couple stress hybrid nanofluid - Ali Rehman; Ma Chau Khun; Dolat Khan; Kamal Shah; Thabet Abdeljawad (South African Journal of Chemical Engineering, 2023)
The insights of this study are implemented in a mathematical model with practical applications in industry, where they improve heat transport and minimize energy usage. The influence of the form factor on the radiative characteristics of a magnetohydrodynamic (MHD) pair stress hybrid nanofluid on a contracting surface is analyzed, along with the stability of the system as a whole. Enhancing the heat transfer ratio is the primary objective of this research because of its importance in the engineering and industrial fields. Nonlinear partial differential equations (PDEs) are formulated as a means of approaching the issue by taking into account the conservation principles of momentum and energy. Using a similarity transformation and thermophysical features, these PDEs are converted into ODEs. The resultant ODEs are solved using the approximate analytical approach known as Homotopy Analysis approach (HAM). The consequence of the relevant parameters, including couple stress parameter, magnetic field parameter, velocity ratio parameter, Prandtl number and Eckert number, on temperature distribution, Nusselt's number, velocity profile, and the skin friction are interrogated with the help of graphical representation. The velocity filed decreases with the increasing value of couple stress parameter, magnetic field parameter, and velocity ratio parameter. The temperature filed is increasing with the increasing value of Eckert number. The authors examine the convergence and stability of the problem using tables, graphs, and a dual solution strategy. In light of the significant difficulty encountered in heat transfer applications for cooling equipment and devices across a wide range of industries including automotive, microelectronics, defense, and manufacturing, this theoretical approach aims to positively contribute towards improving the heat transfer ratio to meet the demands of these sectors.